Tourism Potential Development Strategy in the Malinau Regency through Community-Based Tourism Approach - Nopis Muhramsyah Ishak; Milwan Milwan; Riswanda Riswanda (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
This study aims to analyze tourist potential development strategies and factors that influence the development of tourism potential through a community-based tourism approach in the Malinau Regency. The theory used is the operationalization of the concept of Community-Based Tourism with social indicators, economic, cultural, and environmental dimensions using SWOT analysis. The following research results are obtained: strength that is owned is reliable human resources, high leadership support, and a sufficient number of personnel. The weakness is still limited professional human resources in the field of tourism. In addition to its natural potential, attractions are also an opportunity in the tourism sector of Malinau Regency. The threats faced are tourism competition between other tourist objects. The strategy for developing tourism potential can be done is to optimize strengths, look for new tourism potentials that are unique and different from other tourist destinations, create a tourism brand of the regency, development of infrastructure, tourism promotion, and marketing. While the influencing factors are accessibility, budget, and regional policies. Penelitian ini menganalisis strategi pengembangan dan faktor yang memengaruhi pengembangan potensi wisata melalui pendekatan pariwisata berbasis masyarakat di Kabupaten Malinau. Teori yang digunakan adalah operasionalisasi konsep community based tourism dengan indikator sosial, ekonomi, budaya, dan lingkungan yang dianalisis dengan teknik SWOT. Hasil penelitian sebagai berikut: kekuatan yang dimiliki adalah sumber daya manusia yang handal, dukungan pimpinan, dan jumlah personel yang cukup. Kelemahannya terdapat pada masih terbatasnya sumber daya manusia murni dibidang pariwisata. Selain potensi alamnya, daya tarik lainnya adalah peluang di sektor pariwisata. Ancamannya adalah persaingan di bidang pariwisata dengan objek wisata lain. Strategi pengembangan potensi wisata dilakukan melalui optimalisasi kekuatan, yaitu mencari potensi wisata baru yang unik, menciptakan brand pariwisata kabupaten, mengembangkan infrastruktur, melakukan promosi, dan memasarkan pariwisata. Sementara itu, faktor yang memengaruhi adalah aksesibilitas, anggaran, dan kebijakan daerah.